2008
DOI: 10.1021/jp8023414
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Angular Dependence of the Single-Photon Ionization of Aligned N2 and CO2

Abstract: By combining a state-of-the-art high-harmonic ultrafast soft X-ray source with field-free dynamic alignment, we map the angular dependence of molecular photoionization yields for the first time for a nondissociative molecule. The observed modulation in ion yield as a function of molecular alignment is attributed to the molecular frame transition dipole moment of single-photon ionization to the X, A and B states of N2(+) and CO2(+). Our data show that the transition dipoles for single-photon ionization of N2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
74
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 30 publications
(45 reference statements)
12
74
1
Order By: Relevance
“…Zhao et al [37] suggested that the experiment of Pavičić et al [34] should be reexamined. They compared their CO 2 data with the experiment of Thomann et al [46] which agrees much better with MO-ADK and TDSE calculations. Although there are some experimental issues, we also think • , for three values of intensity.…”
Section: B Angular Dependencesupporting
confidence: 59%
“…Zhao et al [37] suggested that the experiment of Pavičić et al [34] should be reexamined. They compared their CO 2 data with the experiment of Thomann et al [46] which agrees much better with MO-ADK and TDSE calculations. Although there are some experimental issues, we also think • , for three values of intensity.…”
Section: B Angular Dependencesupporting
confidence: 59%
“…Knowledge of molecular orientation in most valence-shell photoionization experiments requires using laser-induced impulsive pre-alignment techniques [6] when the ion does not dissociate, thus necessitating short-pulsed XUV sources for spectroscopy like high-order harmonic generation (HHG) [7], femtosecond sliced synchrotrons [8], or freeelectron lasers [9]. Among these, HHG is unique in that it allows for complete characterization of the complex transition dipole matrix element in both magnitude (the cross section) and phase.…”
mentioning
confidence: 99%
“…The physics responsible for this effect is a subject of hot debate (see, e.g., [7,10,11,13]), including the possible contribution of multiphoton resonances ignored in the tunneling picture [10], or multiple ionic states (multiple orbitals) [13]. The extreme sharpness of the peaks in [9], not observed in [14] and questioned in [7,10], might indeed be related to the artifacts in the deconvolution procedure (see [10]), which is required to extract the ionization rates when dealing with imperfect molecular alignment. However, the rotation of the ionization peaks to about 45 was confirmed [15].…”
mentioning
confidence: 99%